Edukasi Urgensi Digital Marketing bagi UMKM di Kota Denpasar - Wulandari, Riza; Lilis Yuningsih; Tria Hikmah Fratiwi; I Wayan Gede Lamopia (Insan Kreasi Media, 2023)
Digital marketing is still not thoroughly known by business people. The lack of equal distribution of literacy education regarding information technology, especially in digital marketing, is still a major problem that must be resolved immediately. In addition, there is a lack of resources willing to provide training for MSMEs. The purpose of this community service activity is to analyze and educate the importance of digital marketing for business actors, namely MSMEs in Denpasar City. This activity uses a qualitative method where the data collection technique begins with observation, then interviews, followed by educational transfer. The result of this community service activity is that there are still many MSMEs that have not implemented digital marketing, so that educational transfer activities are considered quite successful in having an impact on MSMEs. The results of this activity are recommended to the academic community or stakeholders to provide digital marketing training evenly. So that business actors in the future will be ready to be competitive.